Gastrointestinal transit of extruded or pelletized diets in pacu fed distinct inclusion levels of lipid and carbohydrate - Honorato, Claucia Aparecida; Almeida, Luciana Cristina de; Nunes, Cleujosí da Silva; Carrilho, Elma Neide Vasconcelos Martins; Moraes, Gilberto (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the effect of pelletized or extruded diets, with different levels of carbohydrate and lipid, on the gastrointestinal transit time (GITT) and its modulation in pacu (Piaractus mesopotamicus). One hundred and eighty pacu juveniles were fed with eight isonitrogenous diets containing two carbohydrate levels (40 and 50%) and two lipid levels (4 and 8%). Four diets were pelletized and four were extruded. Carbohydrate and lipid experimental levels caused no changes to the bolus transit time. However, the bolus permanence time was related to diet processing. Fish fed pelletized diets exhibited the highest gastrointestinal transit time. Regression analysis of bolus behavior for pelletized and extruded diets with 4% lipid depicted different fits. GITT regression analysis of fish fed 8% lipid was fitted to a cubic equation and displayed adjustments of food permanence, with enhanced utilization of the diets, either with extruded or pelletized diets. GITT of fish fed extruded diets with 4% lipid was adjusted to a linear equation. The GITT of pacu depends on the diet processing and is affected by dietary levels of lipid and carbohydrate.